PENGARUH PENANAMAN MODAL ASING DAN PENANAMAN MODAL DALAM NEGERI TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN LOMBOK BARAT TAHUN 2014–2023: The Effect of Foreign Direct Investment And Domestic Investment on the Regional Gross Domestic Product of West Lombok Regency, 2014–2023 - Kurniawan, Budi; Harsono, Iwan; Suriadi, Irwan (Ganec Swara, 2026)
This study aims to analyze the effect of foreign direct investment (FDI) and domestic direct investment (DDI) on the Gross Regional Domestic Product (GRDP) of West Lombok Regency. The study employs a quantitative associative approach using secondary time-series data from 2014 to 2023 obtained from the Central Statistics Agency and agencies related to investment. Data analysis was conducted using multiple linear regression with EViews 10, accompanied by tests of classical assumptions, t-tests, F-tests, and the coefficient of determination. The results indicate that, when analyzed individually, FDI has a negative and significant effect on RDP, while DDI has a positive but insignificant effect on RDP. When analyzed simultaneously, both FDI and DDI have a significant effect on the RDP of West Lombok Regency. The coefficient of determination indicates that 65.75% of the variation in GRDP can be explained by FDI and DDI, while the remainder is influenced by other variables outside the model. These findings suggest that investment continues to play a crucial role in regional economic growth, but its effectiveness is strongly influenced by the quality of investment, the target sector, and its alignment with the local economic structure.